Myoblast-derived ADAMTS-like 2 promotes skeletal muscle regeneration after injury - Nandaraj Taye; Levon Rodriguez; James C. Iatridis; Woojin M. Han; Dirk Hubmacher (npj Regenerative Medicine, 2024)
Abstract Skeletal muscle regeneration and functional recovery after minor injuries requires the activation of muscle-resident myogenic muscle stem cells (i.e. satellite cells) and their subsequent differentiation into myoblasts, myocytes, and ultimately myofibers. We recently identified secreted ADAMTS-like 2 (ADAMTSL2) as a pro-myogenic regulator of muscle development, where it promoted myoblast differentiation. Since myoblast differentiation is a key process in skeletal muscle regeneration, we here examined the role of ADAMTSL2 during muscle regeneration after BaCl2 injury. Specifically, we found that muscle regeneration was delayed after ablation of ADAMTSL2 in myogenic precursor cells and accelerated following injection of pro-myogenic ADAMTSL2 protein domains. Mechanistically, ADAMTSL2 regulated the number of committed myoblasts, which are the precursors for myocytes and regenerating myofibers. Collectively, our data support a role for myoblast-derived ADAMTSL2 as a positive regulator of muscle regeneration and provide a proof-of-concept for potential therapeutic applications.